Behavioral Determinants of IVA Inspection in Women of Childbearing Age - Lifiah Ninja Astuti; La Ode Ali Hanafi; Juslan (Universitas Mandala Waluya, 2021)
Data from the Jati Raya Health Center UPTD found that the number of women of childbearing age who did the IVA examination was still lacking. This study aimed to determine the factors related to the Acetic Acid Visual Inspection (IVA) as early detection of cervical cancer in women of childbearing age in the working area of Jati Raya Public Health Center in Kendari City. This study employed an observational analytic method with a Cross-Sectional Study approach. The population amounted to 488 people with a total sample of 83 people, using simple random sampling. The method of analysis used the Chi-Square test. The results of the study showed that knowledge with value X2count=13.414>X2table=4.605, attitude with value X2count=31.867>X2table=2.705, and health workers support with value X2count=0.163>X2table=2.705. In conlusion, there was a relationship between knowledge and attitude with IVA as early detection of cervical cancer in women of childbearing age and there was no relationship between the health workers support and IVA as early detection of cervical cancer in women of childbearing age. It is recommended to the Jati Raya Health Center to increase socialization and provide information about the implementation of the IVA program.